The Financial Stability Board and Switzerland's WiR-Credit Mechanism. Issue 4 (2nd October 2019) - Phillips, Emir; Desmoulins-Lebeault, Francois
Abstract: The incentives banks face, such as the Basel Capital Accords, motivate them to favor lending with collateralized assets, rather than lending to Small-Medium Enterprises (SMEs), with associated profound economic consequences for society. Since the 1970s there has not been any direct oversight of whether or not credit contributes to GDP. We need a macroeconomic policy tool that can discriminate among different categories of credit extended to curb speculation in existing assets (non-GDP) and promote new business investment (GDP). Government money creation and private credit growth are often presumed the only two ways to enhance nominal demand, yet the Swiss Economic Circle (Wirtschaftsring-Genossenschaft or WIR) is a Swiss Bank whose creation of purchasing power for SMEs has counter-cyclically stabilized the Swiss economy for over 80 years. The Financial Stability Board (FSB) should create localized credit-creation architectures utilizing a Swiss-WIR type currency to funnel credit that reflects systemic and macroeconomic risks that individually will never be rational for banks left to themselves.